Study on coccidia infection and species in Cyprus Shami goat population. - Tahir, Mohamad Salim; Tengku Ibrahim, Tengku Azmi; Babjee, Shaik Mohamed Amin (2011)
A survey was undertaken to determine the prevalence of coccidian and helminth infections in the Cyprus Syami goats in two goat farms in the states of Pahang and Negeri Sembilan. The burden of coccidiaoocysts and helminth eggs were determined by the McMaster technique. Identification of Eimeria species was carried out following oocyst sporulation in 2.5% Potassium dichromate solution. The burden of helminthes and coccidia in terms of egg and oocyst counts per gram of faeces was high especially in young animals under the extensive management system. Eimeriaoocysts were found in all faecal samples examined. The species of coccidia identified were E. ninaekohlyakimovae, E. arloingi, E. christenseni, E. hirci, E. alijevi, E. jolchijevi, E. caprina, E. caproving and E. pallida. The most prevalent species identified was E. arloingi, found in 71% of the samples followed by E. Ninakohlyakimovae (67%), e. christenseni (63%) and E. alijevi (61%). Other species present were E. hirci, E. jolchijevi, E. caprovina, E. caprina and E. pallida in 34, 22, 12, 9 and 4% of the faecal samples examined respectively. Oocyst counts were significantly higher in animals below 8 months and in animals kept under extensive management system (P<0.05). High oocyst counts were mainly of non-pathogenic species. High coccidial infection was found to be directly related ot poor hygienic conditions in the management system. Morbidity rates in kids could not be related to the intensity of coccidial infections.